Coronavirus pandemic highlights critical gaps in rural Internet access for migrant and seasonal farmworkers: a call for partnership with medical libraries. - Lee, Joseph G. L.; LePrevost, Catherine E.; Harwell, Emery L.; Bloss, Jamie E.; Cofie, Leslie E.; Wiggins, Melinda F.; Firnhaber, Gina C. (Journal of the Medical Library Association)
Migrant and seasonal farmworkers, who are essential workers in the coronavirus global public health emergency, face unique risks to their health as well as longstanding health inequities. This commentary highlights these risks and argues that Internet access represents an underappreciated but critical part of the public health response. The authors first discuss the unique risks farmworkers face. We note the importance of Internet access in the time of physical distancing, the fact that many health outreach workers are no longer visiting camps, the need for telemedicine infrastructure, and the role of Internet access in providing connections to families in communities of origin. We describe existing efforts that have been implemented in North Carolina to raise awareness among public health and health promotion practitioners and researchers. The current coronavirus pandemic demands the attention of medical libraries, public health practitioners, and policy makers to address the digital divide for farmworkers and their families.